Evaluation of C-Reactive Protein, Neutrophil-To-Lymphocyte Ratio, and Absolute Neutrophil Count as Simple Diagnostic Markers for Spontaneous Bacterial Peritonitis - Putri, Ayu Sekarani Damana; Supriono, Supriono; Tonowidjojo, Vera Diana; Fitriani, Junjun; Utama, Gede Nanda; Muthmainah, Andi Alfia; Asrinawati, Andi Nur (Journal of Health and Nutrition Research, 2025)
Spontaneous bacterial peritonitis (SBP) is a serious complication of liver cirrhosis with high morbidity and mortality. Early diagnosis is crucial; however, ascitic fluid analysis is invasive and often yields a low culture positivity rate. This study aimed to evaluate the diagnostic performance of C-reactive protein (CRP), absolute neutrophil count (ANC), and neutrophil-to-lymphocyte ratio (NLR) as non-invasive markers for the early detection of SBP. A prospective observational study was conducted on 90 liver cirrhosis patients with ascites undergoing diagnostic paracentesis at Saiful Anwar Hospital, Indonesia. CRP, ANC, and NLR levels were compared between the SBP and non-SBP groups. Receiver operating characteristic (ROC) curves were used to assess diagnostic accuracy, and logistic regression identified independent predictors. NLR and ANC levels were significantly higher in SBP patients (p = 0.004 and p = 0.033, respectively), while the difference in CRP levels was not statistically significant (p = 0.372). NLR showed the best performance (sensitivity 81.8%, specificity 68.2%) at a cut-off of 6.8 and was independently associated with SBP (OR = 11.09, p = 0.019). ANC had similar sensitivity but lower specificity, while CRP demonstrated the weakest predictive value. In conclusion, NLR and ANC are emerging as promising, simple, and cost-effective non-invasive biomarkers for the early screening of SBP in cirrhotic patients, particularly in settings where paracentesis is not readily available. NLR, in particular, holds significant diagnostic value. Conversely, CRP may be less reliable in this patient population. Larger multicenter studies are needed to validate these findings